110k views
2 votes
Factor completely 2x^2+9x+4

2 Answers

6 votes

Answer:

1.) x = -4 OR

2.) x = -1/2 = -0.500

Explanation:

4.2 Solving 2x2+9x+4 = 0 by Completing The Square .

Divide both sides of the equation by 2 to have 1 as the coefficient of the first term :

x2+(9/2)x+2 = 0

Subtract 2 from both side of the equation :

x2+(9/2)x = -2

Now the clever bit: Take the coefficient of x , which is 9/2 , divide by two, giving 9/4 , and finally square it giving 81/16

Add 81/16 to both sides of the equation :

On the right hand side we have :

-2 + 81/16 or, (-2/1)+(81/16)

The common denominator of the two fractions is 16 Adding (-32/16)+(81/16) gives 49/16

So adding to both sides we finally get :

x2+(9/2)x+(81/16) = 49/16

Adding 81/16 has completed the left hand side into a perfect square :

x2+(9/2)x+(81/16) =

(x+(9/4)) • (x+(9/4)) =

(x+(9/4))2

Things which are equal to the same thing are also equal to one another. Since

x2+(9/2)x+(81/16) = 49/16 and

x2+(9/2)x+(81/16) = (x+(9/4))2

then, according to the law of transitivity,

(x+(9/4))2 = 49/16

We'll refer to this Equation as Eq. #4.2.1

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of

(x+(9/4))2 is

(x+(9/4))2/2 =

(x+(9/4))1 =

x+(9/4)

Now, applying the Square Root Principle to Eq. #4.2.1 we get:

x+(9/4) = √ 49/16

Subtract 9/4 from both sides to obtain:

x = -9/4 + √ 49/16

Since a square root has two values, one positive and the other negative

x2 + (9/2)x + 2 = 0

has two solutions:

x = -9/4 + √ 49/16

or

x = -9/4 - √ 49/16

Note that √ 49/16 can be written as

√ 49 / √ 16 which is 7 / 4

Solve Quadratic Equation using the Quadratic Formula

4.3 Solving 2x2+9x+4 = 0 by the Quadratic Formula .

According to the Quadratic Formula, x , the solution for Ax2+Bx+C = 0 , where A, B and C are numbers, often called coefficients, is given by :

- B ± √ B2-4AC

x = ————————

2A

In our case, A = 2

B = 9

C = 4

Accordingly, B2 - 4AC =

81 - 32 =

49

Applying the quadratic formula :

-9 ± √ 49

x = —————

4

Can √ 49 be simplified ?

Yes! The prime factorization of 49 is

7•7

To be able to remove something from under the radical, there have to be 2 instances of it (because we are taking a square i.e. second root).

√ 49 = √ 7•7 =

± 7 • √ 1 =

± 7

So now we are looking at:

x = ( -9 ± 7) / 4

Two real solutions:

x =(-9+√49)/4=(-9+7)/4= -0.500

or:

x =(-9-√49)/4=(-9-7)/4= -4.000

Two solutions were found :

x = -4

x = -1/2 = -0.500

Processing ends successfully

User PanosPlat
by
5.4k points
2 votes

Answer:

(2x + 1) (x + 4) hope it helps

User Amarnath
by
5.8k points